Hakikat Anak dalam Perspektif Pendidikan Islam - Yogaswara, Angga (Tsamratul Fikri | Jurnal Studi Islam, 2019)
Children are an investment in the future, because they are born carrying a pile of hopes. The issue of educating children in Islam is a very important issue. The process of Islamic education does not only begin when the child is born, but since in the womb, Islamic education has begun, even since the marriage was prepared. Thus, Islam which originates from the Qur'an and Hadith strongly upholds the values of Education. Baesd on the importance of the position of children in the family, then Islam also called for educating and managing the child's potential seriously. This call is to prevent children from being abandoned so that they grow into weak human beings in all matters both intellectually and socio-emotionally, but Islam pays attention to the formation of children's character to be better. In Islam there is the term of human being, this is the ultimate goal of Islamic education.